2015
DOI: 10.1121/1.4919337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contextual cues on speech recognition in simulated electric-acoustic stimulation

Abstract: Low-frequency acoustic cues have shown to improve speech perception in cochlear-implant listeners. However, the mechanisms underlying this benefit are still not well understood. This study investigated the extent to which low-frequency cues can facilitate listeners' use of linguistic knowledge in simulated electric-acoustic stimulation (EAS). Experiment 1 examined differences in the magnitude of EAS benefit at the phoneme, word, and sentence levels. Speech materials were processed via noise-channel vocoding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 36 publications
7
26
2
Order By: Relevance
“…Considered in isolation, this finding suggests that continuous periodicity/harmonicity information carried in the cLPHC can support improved identification of word and syllable boundaries (i.e., enhanced segmentation), as suggested previously by Kong et al (2015). However, the data obtained in experiment 1 with gated vocoder speech showed that similar bimodal benefit was achieved when the low-frequency ear received noise-filled LPHCs (gV þ nfLPHC condition) as when it received continuous LPHCs (gV þ cLPHC condition).…”
Section: A Role Of Lf Continuity In Bimodal Benefitsupporting
confidence: 56%
See 4 more Smart Citations
“…Considered in isolation, this finding suggests that continuous periodicity/harmonicity information carried in the cLPHC can support improved identification of word and syllable boundaries (i.e., enhanced segmentation), as suggested previously by Kong et al (2015). However, the data obtained in experiment 1 with gated vocoder speech showed that similar bimodal benefit was achieved when the low-frequency ear received noise-filled LPHCs (gV þ nfLPHC condition) as when it received continuous LPHCs (gV þ cLPHC condition).…”
Section: A Role Of Lf Continuity In Bimodal Benefitsupporting
confidence: 56%
“…Kong et al (2015) showed that simulated bimodal listeners were able to achieve significant amounts of bimodal benefit when receiving continuous vocoded sentences in one ear and a continuous LPHC in the other. Given that all speech materials were presented in quiet, they attributed the observed bimodal benefit to improved speech segmentation (i.e., enhanced definition of syllable and word boundaries) when robust harmonicity cues were present in the bimodal listening condition.…”
Section: A Role Of Lf Continuity In Bimodal Benefitmentioning
confidence: 99%
See 3 more Smart Citations